2013
DOI: 10.1111/cdev.12073
|View full text |Cite
|
Sign up to set email alerts
|

Child‐Care Subsidies and School Readiness in Kindergarten

Abstract: The federal child care subsidy program represents one of the government’s largest investments in early care and education. Using data from the nationally representative Early Childhood Longitudinal Study – Birth Cohort (ECLS-B), this paper examines associations, among subsidy-eligible families, between child care subsidy receipt when children are 4 years old and a range of school readiness outcomes in kindergarten (sample n ≈ 1,400). Findings suggest that subsidy receipt in preschool is not directly linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 42 publications
1
27
1
Order By: Relevance
“…Parents who stated that the primary arrangement was free home‐based care were categorized as subsidy recipients if the provider also reported that he or she was licensed or part of a family child‐care network, supplied care in the provider's home, and cared for three or more unrelated children. This last condition was used to differentiate free, informally provided home‐based care (e.g., that provided by a grandparent) from subsidized home‐based care where the subsidy covers the entire cost (for more discussion of the coding of subsidy receipt and nonreceipt at the preschool wave, see Johnson et al., ; Johnson, Martin, & Brooks‐Gunn, . )…”
Section: Methodsmentioning
confidence: 99%
“…Parents who stated that the primary arrangement was free home‐based care were categorized as subsidy recipients if the provider also reported that he or she was licensed or part of a family child‐care network, supplied care in the provider's home, and cared for three or more unrelated children. This last condition was used to differentiate free, informally provided home‐based care (e.g., that provided by a grandparent) from subsidized home‐based care where the subsidy covers the entire cost (for more discussion of the coding of subsidy receipt and nonreceipt at the preschool wave, see Johnson et al., ; Johnson, Martin, & Brooks‐Gunn, . )…”
Section: Methodsmentioning
confidence: 99%
“…The subsequent effect of the home setting on the child can influence both cognitive development and development of the prefrontal cortex. In the realm of cognitive development, a student's home environment has been shown to affect his receptive vocabulary (Razza, et al, 2010) as well as his math scores (Johnson, Martin, & Brooks-Gunn, 2013). The combination of low income and low quality home environment has also been shown to predict difficulties with executive functioning (Raver, McCoy, Lowenstein, & Pess, 2013).…”
Section: Home Environmentmentioning
confidence: 99%
“…Much of this research capitalizes on rich, national or multi-state survey data to describe the characteristics of subsidy recipients (e.g., Herbst, 2008; Johnson, Martin, & Brooks-Gunn, 2011; Lee et al, 2004; Tekin, 2005; 2007), examine the relationship between subsidy receipt and child care choices (e.g., Crosby, Gennetian, & Huston, 2005; Johnson, Ryan, & Brooks-Gunn, 2012; Ryan, Johnson, Rigby, & Brooks-Gunn, 2011), and understand the implications of subsidy use for child and family well-being (e.g., Hawkinson, Griffen, Dong, & Maynard, 2013; Herbst & Tekin, 2010a; 2010b; 2011; 2012; Johnson, Martin, & Brooks-Gunn, in press). …”
Section: Introductionmentioning
confidence: 99%
“…The ECLS-K has been used in multiple published studies linking subsidy receipt to child and family outcomes (e.g., Herbst & Tekin, 2010a; 2010b). Similar questions appear in other nationally representative studies or multi-state studies, including the Early Childhood Longitudinal Study–Birth Cohort (ECLS-B), the Fragile Families and Child Wellbeing Study (FFCWS), the National Survey of America’s Families (NSAF), the Survey of Income and Program Participation (SIPP), and the National Household Education Survey (NHES), (see Appendix A for exact wording of questions across these data sets; Blau & Tekin, 2007; Forry, 2009; Hawkinson et al, 2013; Ha & Johnson, 2012; Herbst, 2008; Herbst & Tekin, 2010a; 2010b; 2011; 2012; Johnson, Martin, & Brooks-Gunn, in press; Tekin, 2007). In the context of this large and growing body of subsidy research, it is important to investigate the degree to which parental reports of subsidy might overlap with measures of subsidy receipt gathered from alternate sources, such as child care providers.…”
Section: Introductionmentioning
confidence: 99%